Prediction of mesio-distal crown diameter of the unerupted lower premolars - Khidair A Salman; Hind T Jarjees (University of Mosul, College of Dentistry, 2004)
The purpose of this study was to det-ermine the more accurate method for pre-dicting the width of unerupted mandibular premolar of mixed dentition patients, whe-ther by the multiple regression analysis method or by radiographic measurements of deciduous molars width method. Multiple regression analysis method was performed on data derived from 108 children (62 females and 46 males) aged 9-12 years old. These children were selec-ted from primary schools located in differ-ent areas of Mosul City. All subjects had normal Class I molar relationship with mixed dentition (the right and left perman-ent centrals, laterals and first molars, and right and left primary canines and first and second molars). The data were statistically analysed using Statistical Package for Soc-ial Statistics. The results revealed that there were no significant differences in mesio-distal crown diameter between right and left sides of both unerupted premolars and deciduous molars. All the teeth in males were larger in mesio-distal crown dia-meter than females. Also, the results of the present study indicated that there was a positive correlation between most of the teeth, individual teeth and groups of teeth. There was a difference in the means bet-ween the mesio-distal crown diameter of deciduous molars and unerupted premo-lars. The present results used to generate a formula "linear regression equation" that can be used clinically to affect prediction depending on the mesio-distal width of individual deciduous molars.